SOVIET SECRET POLICY IN KAZAKHSTAN IN THE EARLY 20TH CENTURY AND ITS CONSEQUENCES - Can, Mehmet (Journal of Oriental Studies, 2025)
As a part of the Union of Soviet Socialist Republics between 1917 and 1990, Kazakhstan was subjected to a serious process of social, cultural, and geographical fragmentation. During this period, Kazakhs had a difficult struggle for existence to preserve their national identity. The social, cultural, and economic transformations that Kazakh society faced in this process should be analyzed comprehensively. Because emotional approaches are an important obstacle to a full understanding of Kazakhstan’s past, this situation is further complicated by severing the country’s historical ties, falsifying archival records, and the systematic destruction of its past. Since the collapse of the Soviet Union, researchers have gained access to geography and have been able to study it, which has led to more objective and innovative approaches to the subject. This new research provides an important opportunity for a deeper understanding of Kazakhstan’s history and the transformations of its society. Keywords: Cultural, Kazakh Society, Transformation